Long-term working-time accounts and life-course policies: Preliminary results of a representative company survey - Philip Wotschack; Eckart Hildebrandt (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
The paper introduces the basic concept and functioning of long-term workingtime accounts and discusses major trends, risks and opportunities with regard to life-course oriented working-time adjustments. It gives a detailed overview of the distribution and use of long-term working-time accounts in Germany. This overview is based on initial multivariate analyses of a representative company survey that was carried out in 2005. The main questions concern the individual options and opportunities offered by long-term working-time accounts and the characteristics of their distribution. We examine effects of firm size, sector, demand fluctuations, economic performance, personnel policy, industrial relations, and workforce composition. There is empirical evidence that the distribution and use of long-term working-time accounts is strongly influenced by company size and the presence of a works- or staff council in the company. Larger companies with works or staff councils have more frequently long-term working-time accounts and use them predominantly for early or progressive retirement options, even more when the share of male employees in the company is high. – – Der Artikel stellt das relativ neue Arbeitszeitinstrument betrieblicher Langzeitkonten vor und untersucht deren Entwicklung und Potenziale hinsichtlich einer lebensphasenorientierten Arbeitszeitgestaltung. Anhand multivariater Auswertungen wird die Verbreitung und Nutzung von Langzeitkonten in der Bundesrepublik Deutschland analysiert. Basis ist eine repräsentative Unternehmensbefragung, die im Herbst 2005 durchgeführt wurde. Leitend ist die Frage nach Unterschieden der Verbreitung von Langzeitkonten und den damit verbundenen Arbeitszeitoptionen für die Beschäftigten. Dabei werden grundlegende Betriebsmerkmale berücksichtigt, wie Größe, Marktsituation, Personalpolitik, industrielle Beziehungen und Beschäftigungsstruktur. Es zeigen sich deutliche Unterschiede nach der Betriebsgröße und dem Vorhandensein einer betrieblichen Interessenvertretung. Größere Unternehmen mit Betriebs- oder Personalrat verfügen häufiger über Langzeitkonten und nutzen diese vorrangig für den vorzeitigen oder gleitenden Ruhestand.
Keywords: 330; Arbeitszeitflexibilisierung; Erwerbsverlauf; Betriebliche Sozialleistungen; Deutschland